Motives to practice physical education and sports activities among pupils of the final sections in secondary education / M. Kenioua and A. Aboumasdjed - Kenioua, M.; Aboumasdjed, A. (Faculty of Sports Science and Recreation, 2017)
This study aims to find out" Motives to practice physical education and sports activities among pupils of the final sections Of secondary education». It tried to answer at some questions regarding the pupils' differences in respect to sexual variation. This study chose "attitude scale to words physical activity " who discovered it "keynon" and translate it " mohamed assen aalaoui". This search was practiced at choice formed 240 pupils (male and female) secondary school - jijel city .There after distributed and gathered the questionnaires and presenting , and recording the consequence for know the statistic differences between scientific pupils and literary pupils. The results also showed that there were statistically significant differences among students for a changing sex, but as a relative and this in all dimensions studied.